1996
DOI: 10.1007/bf02359410
|View full text |Cite
|
Sign up to set email alerts
|

Formation of taste aversion and preference in protein synthesis inhibition in rats

Abstract: The investigation was devoted to the role of the synthesis of protein and peptide factors during the formation of chemosensory memory in rats. Two models of gustatory memorization were used: conditioned taste aversion (CTA), induced by the association of the taste of saccharine with a toxic injection of lithium chloride, and enhanced taste preference (ETP), induced by the influence of preliminary drinking of a saccharine solution on its repeat consumption. It was found that, under conditions of the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Our previous studies demonstrated that acute microinfusion of BDNF in anesthetized adult rats 24 h before CTA training enhances the retention of this task (Castillo et al, 2006). Moreover, it has been observed that protein translation inhibition impairs CTA consolidation but not acquisition (Rosenblum et al, 1993; Serova et al, 1996; Berman and Dudai, 2001; Moguel-Gonzalez et al, 2008) and we recently reported that acute intracortical delivery of BDNF reverses the deficit in CTA memory, caused by inhibition of IC protein synthesis due to anisomycin administration (Moguel-Gonzalez et al, 2008). These evidences suggest that BDNF is an essential protein synthesis product for the establishment of the CTA–LTM.…”
Section: Introductionmentioning
confidence: 86%
“…Our previous studies demonstrated that acute microinfusion of BDNF in anesthetized adult rats 24 h before CTA training enhances the retention of this task (Castillo et al, 2006). Moreover, it has been observed that protein translation inhibition impairs CTA consolidation but not acquisition (Rosenblum et al, 1993; Serova et al, 1996; Berman and Dudai, 2001; Moguel-Gonzalez et al, 2008) and we recently reported that acute intracortical delivery of BDNF reverses the deficit in CTA memory, caused by inhibition of IC protein synthesis due to anisomycin administration (Moguel-Gonzalez et al, 2008). These evidences suggest that BDNF is an essential protein synthesis product for the establishment of the CTA–LTM.…”
Section: Introductionmentioning
confidence: 86%
“…Control injections consisted of sterile saline administered via the same routes and volumes as the treatment injections. Prior reports using the same dose and route of CXM administration have suggested that the PSI, although sufficient to disrupt the acquisition of CTA, is inhibited by only 43% in the rat brain (Serova et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The conditioned response (CR) resulting from this pairing of flavor with illness is manifested by the animal's subsequent avoidance of the CS. Of interest to the present study are those findings indicating that CTA is dependent on de novo protein synthesis in the brain (Berman & Dudai, 2001; Serova, Solov'ea, Lagutina, & Obukhova, 1996; Tucker & Gibbs, 1976, 1979; Tucker & Oei, 1982). CTA studies have demonstrated that PSI infusions into the gustatory cortex impair acquisition (Rosenblum, Meiri, & Dudai, 1993); infusions into the central nucleus of the amygdala impair consolidation (Bahar, Dorfman, & Dudai, 2004); and infusions into the basolateral nucleus (Bahar et al, 2004), insular cortex (Berman & Dudai, 2001), or the ventromedial prefrontal cortex (Akirav et al, 2006) disrupt extinction.…”
mentioning
confidence: 94%
“…There is evidence that long-term CTA memory requires protein synthesis. Administration of general protein synthesis inhibitors into the lateral ventricles (Tucker and Gibbs 1976;Serova et al 1995) or cerebral cortex (Rosenblum et al 1993) attenuates long-term expression of CTAs. Long-term CTA has been attenuated also by inhibiting the synthesis of specific proteins with antisense oligonucleotides: c-Fos or CREB within the amygdala (Lamprecht and Dudai 1996;Lamprecht et al 1997), and c-Fos in the brain stem after fourth-ventricular administration (Swank et al 1996).…”
Section: Discussionmentioning
confidence: 99%